Indigenous women in educational leadership: identifying supportive contexts in Mi'kmaw Kina'matnewey. Issue 6 (1st November 2020) - Robinson, Ingrid M.; White, Robert E.; Robinson, Daniel B.
ABSTRACT: This article is drawn from a larger qualitative case study that examined the leadership context and leadership approaches of five Mi'kmaw women school principals in Mi'kmaw Kina'matnewey (MK), an Aboriginal educational authority, located in Nova Scotia, Canada. This article aims to identify the contextual supports within MK that have enabled Mi'kmaw women educators to obtain and retain positions as principals. The use of a decolonizing methodology positioned the participants to work in partnership with the researcher during data collection and analysis. Data collection and analysis involved the use of one-on-one and sharing circle conversations with the principals. Findings suggest that the social, cultural, and organizational contexts where women lead have had a significant influence on their lives. More specifically, familial, collegial, community, and organizational supports have enabled these women to hold positions as principals and enabled Mi'kmaw cultural revitalization to occur within their school communities. Although the contexts within MK are not reproducible, aspects of the supports within these contexts can be employed by schools and school districts to support the hiring and retention of minoritized members of society in educational leadership.